Platelet Adhesiveness to Glass - Page, R L; Mitchell, J R A (Thrombosis and Haemostasis, 1979)
1. When anticoagulated blood is placed in a rotating glass flask, the blood/air interface initiates platelet aggregation, and the aggregates are trapped on the flask wall, without adhering to it, by the thin film of blood which forms during rotation. The interface; allows CO2 loss so that the pH of the rotating blood rises markedly and this rise is associated with the release of 3H-5HT from platelet. When CO2 diffusion and consequent pH rise is prevented, platelet loss and 3H-HT release are significantly reduced.2. A simple method for assessing the adhesiveness of single platelets to glass using a Neubauer haemocytometer chamber has been developed. The results obtained are independent of platelet number which allows the test to be used in conditions in which abnormal platelet behaviour is associated with a low platelet-count.3. Adhesiveness was negligible in heparinised PRP, and was greater in EDTA PRP than in citrated PRP. Heparin abolished the increased adhesiveness observed with the other anticoagulants and adhesiveness did not seem to be directly related to residual plasma calcium concentrations. Platelets adhered more readily to siliconised glass surfaces than to untreated glass, and adhesion was markedly temperature-dependent, being maximal at 4°C in heparinised PRP, and at 20° C in EDTA PRP.4. Adhesiveness was enhanced by aggregating agents, this enhancement being prevented by inhibitors of aggregation such as the dipyridamole analogue VK 774. Adhesiveness was unaffected by acetyl-salicylic acid.5. Adhesiveness increased markedly after surgical operations and myocardial infarction. Within-person variation was considerable, and the test is of no value in individual patients.